2003
DOI: 10.1007/s00217-002-0655-2
|View full text |Cite
|
Sign up to set email alerts
|

Electric properties of apple purée and pulpy apple juices

Abstract: Results are presented of research, the aim of which has been to determine the selected physicochemical qualities, including electric quantities, of apple purées and pulpy juices obtained from them. The characteristics of the electric properties have covered the measurements of impedance (Z) and effective resistance (R), admittance (Y) and conductance (G), as well as equivalent parallel capacitance (Cp) and equivalent series capacitance (Cs). Changes have been determined in the purée properties relating to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 2 publications
0
14
0
Order By: Relevance
“…Impedance measurements may also prove well in the assessment of moisture content during the heating and drying of potato tubers and carrot roots, and in the detection of artificial chemical additives in liquid food products [18][19][20]. The results of our own studies showed that measurements of electrical parameters (impedance, resistance, admittance, and conductance) may be applied to assess apple puree concentrations in pulpy juices and beverages [2,21], to determine contents of Total Soluble Solids (TSS) in reconstituted apple juices [22], and to determine contents of mineral substances, ash, and dry matter in apple juice [8].…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Impedance measurements may also prove well in the assessment of moisture content during the heating and drying of potato tubers and carrot roots, and in the detection of artificial chemical additives in liquid food products [18][19][20]. The results of our own studies showed that measurements of electrical parameters (impedance, resistance, admittance, and conductance) may be applied to assess apple puree concentrations in pulpy juices and beverages [2,21], to determine contents of Total Soluble Solids (TSS) in reconstituted apple juices [22], and to determine contents of mineral substances, ash, and dry matter in apple juice [8].…”
Section: Introductionmentioning
confidence: 85%
“…These products owe this special role to their biologically-active compounds. From the nutritional perspective, naturally cloudy juices-purees and musts, represent significantly richer sources of bioactive compounds compared to the clear juices due to particles of fruit pulp they contain [1,2]. Significant complexity and time-consumption of methods used to evaluate technological parameters of food products as well as the need for automation of production processes have contributed to a growing interest of scientists in novel methods whose food quality prediction precision would be close to the precision of methods used for direct quality measurement.…”
Section: Introductionmentioning
confidence: 99%
“…2. Scheme of a measuring system of electrical properties of raw materials and food products: Z -impedance, R -resistance, C s -series equivalent capacitance, C pparallel equivalent capacitance, M -measuring device (Pierzynowska-Korniak et al, 2003;_ Zywica et al, 2005). measured parameters in the function of frequency were observed for butter and the greatest for oil, respectively.…”
Section: Conductance Parameters -Admittance (Y)mentioning
confidence: 99%
“…2) elaborated by our research group based on our previous studies with: milk, fruit juices and fruit purée, and meat(Pierzynowska-Korniak et al, 2003;_ Zywica et al, 2005;Banach and _ Zywica, 2010;_ Zywica et al, 2012), but also based on results of investigations published in available research works(Mabrook and Petty, 2003a,b).…”
mentioning
confidence: 99%
“…Measurements were repeated 6 times according to the electric model previously described. [16,17] Next, on the basis of the measurements obtained, specific: impedance (Z sp ), resistance (R sp ), admittance (Y sp ) and conductance (G sp ) were calculated using formulas 4-7: [17] where: l is distance between the electrodes (m), and s is active surface of electrodes (m 2 ). The results of investigations were statistically analyzed using the Statistica™ 6.1 programme.…”
mentioning
confidence: 99%